2014
DOI: 10.4236/jep.2014.510082
|View full text |Cite
|
Sign up to set email alerts
|

Medical Waste Management in China: A Case Study of Xinxiang

Abstract: Due to medical waste's infection and hazard, it can cause potential environmental and public health risks, so medical waste management is of great importance especially in developing countries. The objective of the study was to analyze and assess current status of medical waste management in the light of semi-structured interview in medical institutions and the medical waste disposal centre. As a medium-sized city of China and its respective nature, Xinxiang was selected as the case study. In order to signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Frequently, particularly for more remote and rural hospitals, this funding is not sufficient. In one study conducted in the city of Xinxiang, Henan province, it was found that local medical institutions received little support in terms of transport costs for medical waste management from upper tiers of government to sustain their costs [ 16 ]. In fact, financial support was lacking to the point that many hospitals could not afford to transport their medical waste off-site, despite national requirements that they do so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Frequently, particularly for more remote and rural hospitals, this funding is not sufficient. In one study conducted in the city of Xinxiang, Henan province, it was found that local medical institutions received little support in terms of transport costs for medical waste management from upper tiers of government to sustain their costs [ 16 ]. In fact, financial support was lacking to the point that many hospitals could not afford to transport their medical waste off-site, despite national requirements that they do so.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, financial support was lacking to the point that many hospitals could not afford to transport their medical waste off-site, despite national requirements that they do so. At the same time, the relatively small quantities of medical waste produced by rural or remote hospitals provided little incentive for disposal centers to service these areas to pick up waste [ 14 , 16 ]. Without off-site treatment of medical waste, hospitals had even less of an incentive to enforce proper segregation, packing or disposal of waste.…”
Section: Discussionmentioning
confidence: 99%
“… Tulokhonova and Ulanova (2013) and Nie et al. (2014) have respectively shown that approximately 282,447 tons of medical waste are produced yearly in Africa and nearly 5.22 million people die from the effects of healthcare waste.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors indicate as potential substrates also body parts, blood, chemical drugs, medical devices and syringes, which are very rich in organic matter and can be used as feedstock for biogas production, although possibly raising ethical problems and lack of respect of local cultures (Mohammed et al 2017). The number of hospital centers in China has increased dramatically from 305,000 to 961,830 in space of 10 years and consequently, medical waste has also increased rapidly (Li et al 2014). To enhance the biomass for large-scale application, careful management of hospital waste will increase the potential for biogas production.…”
Section: General Results About China and Africamentioning
confidence: 99%